Konsep Hukum Zakat Sebagai Instrumen Untuk Pemberdayaan Umat Desa Bolihutuo Kecamatan Botumoito Kabupaten Boalemo - Insani, Nur; P, Umar; Beddu, Sumiyati; Darmawati, Darmawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) IAIN Manado, 2023)
The basic concept of zakat is a religious commandment to enhance faith and piety, and at the same time, it is considered the most essential aspect of human life because it provides valuable benefits as an act of worship, purifying the hearts and souls, and bringing blessings to life. However, on the other hand, the expected benefits of zakat have not been fully optimized due to several factors, such as the crisis of trust in zakat management institutions and the lack of awareness among those obligated to pay zakat. As a highly valuable asset, zakat has the potential to address social issues for society, including poverty. To achieve this, it is important for zakat to be managed properly based on the principles of Islamic Sharia as explained in the Qur'an and hadiths.